PALATAL ROTATONIAL FLAP: AN ALTERNATIVE FOR PALATAL PRIMARY INTENTION NEALING - García Linares, Sixto A. (2004)
Objectives- The present clinical study tries to show an alternative for closing of superior bicuspids alveolus to maintain alveolar ridge and to avoid alveolitis because of first intention wound healing. Results. It was observed after 15 days; 12 patients had a complete wound healing of the alveolus and the palate showed a mattress of consistent granulation. A patient discontinued the treatment. Two patients had a wound healing lip to 75%. They didn't register adverse effects: hemorrhage, intense postoperative pain neither alveolitis. Conclusions. The rotational palatal flap is a simple and quick alternative of maintaining the maxillary alveolar ridge Alveolitis is avoided. You can use it for closing of buccosinusal communication when the roots of the second bicuspid penetrale ill the maxillary sillus.